Role of miRNA Let-7 and Its Major Targets in Prostate Cancer. (3rd September 2014) - Wagner, Siegfried; Ngezahayo, Anaclet; Murua Escobar, Hugo; Nolte, Ingo
Abstract : Prostate cancer is worldwide the sixth leading cause of cancer related death in men thus early detection and successful treatment are still of major interest. The commonly performed screening of the prostate-specific antigen (PSA) is controversially discussed, as in many patients the prostate-specific antigen levels are chronically elevated in the absence of cancer. Due to the unsatisfying efficiency of available prostate cancer screening markers and the current treatment outcome of the aggressive hormone refractory prostate cancer, the evaluation of novel molecular markers and targets is considered an issue of high importance. MicroRNAs are relatively stable in body fluids orchestrating simultaneously the expression of many genes. These molecules are currently discussed to bear a greater diagnostic potential than protein-coding genes, being additionally promising therapeutic drugs and/or targets. Herein we review the potential impact of the microRNA let-7 family on prostate cancer and show how deregulation of several of its target genes could influence the cellular equilibrium in the prostate gland, promoting cancer development as they do in a variety of other human malignant neoplasias.